The Speed-Time-Space Structure Curve (Kepler's Law) - Tsapa, Joseph Aaron (Journal of Educational Research and Policies, 2024)
According to Einstein everybody make a curve in space. This curve is the case of gravity. A large body make a large curve. If the body is in velocity than space time curve should be small in the direction of velocity and large in the opposite direction.